Eye Whitening Using Subconjunctival Injections. (December 2015) - Campion, Michael; Campion, Robert J.; Campion, Vincent M.
Introduction: Recent reports have alerted medical providers about the danger of certain eye whitening procedures that involve a combination of removing generous areas of conjunctiva, cautery, laser, and the later use of antimetabolites. This case report describes an alternative technique using subconjunctival injections. This novel procedure may avoid risks associated with previously described techniques. Materials and Methods: The subconjunctival space was entered and lidocaine 2% with epinephrine was injected. White tattoo ink was then injected into the subconjunctival space and spread throughout with external pressure. The patient was observed as to the appearance, longevity, and tolerance of the ink as well as possible side effects. Results: The ink could be spread easily throughout the eye in a homogeneous fashion and remained visibly apparent throughout the observation period. The patient reported mild transient tearing, light sensitivity, and seepage of ink during the first 5 days, but it quickly abated after that time period. Visual acuity, intraocular pressure, and corneal appearance were unchanged throughout the observation period. The appearance of the eyes postoperatively was consistent for 24 months. Conclusions: The technique of using subconjunctival injections as a means to whiten eye appearance is feasible and avoids the risks associated with previously used techniques.